2022
DOI: 10.1038/s41531-022-00286-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of dopaminergic medication on speech in early-stage Parkinson’s disease

Abstract: The effect of dopaminergic medication on speech has rarely been examined in early-stage Parkinson’s disease (PD) and the respective literature is inconclusive and limited by inappropriate design with lack of PD control group. The study aims to examine the short-term effect of dopaminergic medication on speech in PD using patients with good motor responsiveness to levodopa challenge compared to a control group of PD patients with poor motor responsiveness. A total of 60 early-stage PD patients were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Despite providing significant clinical improvement for motor signs in PD, DRT appears to have limited efficacy for improving functional speech outcomes. The majority of studies examining the acute effects of dopaminergic therapy found no significant group-level treatment effects on measures of speech and voice function ( Kompoliti et al, 2000 ; Ho et al, 2008 ; Plowman-Prine et al, 2009 ; Skodda et al, 2010 , 2011 ; Fabbri et al, 2017 ; Whitfield et al, 2018 ; Cavallieri et al, 2021 ; Tykalova et al, 2022 ). However, some studies have reported levodopa-related improvements in acoustic measures of vocal pitch and quality ( Sanabria et al, 2001 ; Lechien et al, 2019 ; Pah et al, 2021 ).…”
Section: Effects Of Pharmacological and Surgical Treatments For Pd On...mentioning
confidence: 99%
“…Despite providing significant clinical improvement for motor signs in PD, DRT appears to have limited efficacy for improving functional speech outcomes. The majority of studies examining the acute effects of dopaminergic therapy found no significant group-level treatment effects on measures of speech and voice function ( Kompoliti et al, 2000 ; Ho et al, 2008 ; Plowman-Prine et al, 2009 ; Skodda et al, 2010 , 2011 ; Fabbri et al, 2017 ; Whitfield et al, 2018 ; Cavallieri et al, 2021 ; Tykalova et al, 2022 ). However, some studies have reported levodopa-related improvements in acoustic measures of vocal pitch and quality ( Sanabria et al, 2001 ; Lechien et al, 2019 ; Pah et al, 2021 ).…”
Section: Effects Of Pharmacological and Surgical Treatments For Pd On...mentioning
confidence: 99%
“…While not controlling for these variables may limit the generalizability of our findings, we do not view the absence of this information as a confound for our results. The purpose of this study was to examine disease classification accuracy based solely on speech function, and there are many cases where speech severity is distinct from disease severity, duration, or medication use (Ball et al, 2002;Barnett et al, 2020;Cavallieri et al, 2021;Fabbri et al, 2017;Rusz, Tykalova, Novotny, Zogala, et al, 2021;Skodda, Flasskamp, et al, 2011;Tykalova et al, 2022). Thus, given the study's focus on speech function, we believe the most critical component to control for was speech severity.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, for the dramatic impairment in quality of life and social isolation brought by speech disorders in PD patients, espically for advanced-stage PD patients, current PD therapeutic approaches, such as dopamine-based pharmacotherapy and deep brain stimulation (DBS) 22 24 , fall short in providing substantial benefits. Personalized and objectively monitored interventions are required for the effective management of speech disorders in PD.…”
Section: Introductionmentioning
confidence: 99%